2019
DOI: 10.1111/isj.12272
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Workaround Practices: the Challenge of Enterprise System Implementations in Multinational Corporations

Abstract: Based on a four-year longitudinal case study of a French multinational corporation (MNC) this research explains how a global enterprise system, initially designed to provide greater control by headquarters across its MNC sites, led to the emergence of unexpected practicesknown as workaroundsin its Chinese subsidiaries. Drawing on concepts from activity theory our findings provide greater theoretical understanding of workarounds in three ways. First, users are involved in collectively constructing and implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 81 publications
0
28
1
Order By: Relevance
“…However, Heath and Porter ( 2019 ) reported that workaround behavior displayed by adopters was either informal and on the individual level, or formal and on an institutional level in response to government-enforced change. Furthermore, workaround is not necessarily a deviant behavior, as posited by Malaurent and Karanasios ( 2020 ), but rather a learning process that intends to find a way to accomplish a goal and complete a task. This kind of deviations are therefore “harmless workarounds that can then be classified as essential or hindrance workarounds” (Choudrie and Zamani, 2016 , p. 144) and the intention for this type of workaround is to get the primary tasks and goals done.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Heath and Porter ( 2019 ) reported that workaround behavior displayed by adopters was either informal and on the individual level, or formal and on an institutional level in response to government-enforced change. Furthermore, workaround is not necessarily a deviant behavior, as posited by Malaurent and Karanasios ( 2020 ), but rather a learning process that intends to find a way to accomplish a goal and complete a task. This kind of deviations are therefore “harmless workarounds that can then be classified as essential or hindrance workarounds” (Choudrie and Zamani, 2016 , p. 144) and the intention for this type of workaround is to get the primary tasks and goals done.…”
Section: Resultsmentioning
confidence: 99%
“…In certain contexts, customization in the form of creative use of technology could be beneficial, but in a safety-critical context, customization that is not planned and is not according to protocols could lead to hazardous outcomes. However, it should be mentioned that Malaurent and Karanasios ( 2020 ) contrasted customization with workaround, stating that workaround is the employees' innovation of using technology in an unexpected way while customization is induced by the organization in a top-down manner.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, task variety positively moderates the effect of system modularity on system exploration. Malaurent and Karanasios (2019) examined how a global enterprise system led to the emergence of unexpected practices (workarounds) based on a four-year longitudinal case study. It was found that users collectively construct and implement workaround practices rather than simply accept or reject an information system.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Structuration and appropriation are the core ideas of AST. Following AST, prior research has extensively examined diversified behaviors related to adaptive IT use, such as feature use and feature extension (Jasperson et al, 2005), appropriation (Fuller and Dennis, 2009), innovativeness with IT (Wang et al, 2013), extended use of enterprise systems (Peng et al, 2018), workarounds of a global enterprise system (Malaurent and Karanasios, 2019). However, prior research mainly examined adaptive IT use at the levels of technology, system or feature.…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the ISJ, we present five articles. In the first article Malaurent and Karanasios (2020), Karanasios report on a longitudinal case study of an enterprise system implementation in a multinational corporation. Drawing on activity theory, the paper examines how the misfits between the enterprise system and its users at the multinational corporation's subsidiary led to the emergence of workaround practices.…”
mentioning
confidence: 99%